2013
DOI: 10.3329/bjar.v37i4.14385
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen and potassium on growth and yield of gladiolus corms

Abstract: 93 cm), the maximum percentage of spikes (88.1%), and corm (97.6%), the heaviest and the largest corm (19.5 g and 4.11 cm, respectively), cent percent flowering sized corm, and the highest corm number and cormel yield (1,20,000 and 1.66 t/ha, respectively). The corm produced from this treatment combination also showed better performances in the next year in respect of plant emergence (100%), florets/spike (13.1), spike and rachis length (82.2 cm and 45.4 cm, respectively), flower stick weight (57.1 g) and perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
7
7
0
Order By: Relevance
“…In May 2012, greater 2012 N rates led to more vigorous growth of 'Immortality' TB iris. These results are consistent with those reported for gladiolus (Gladiolus L.) (Khan et al, 2012) and dahlia (Dahlia Cav.) (Younis et al, 2009) of which the height of plants was improved by higher N fertilizer rates.…”
Section: Discussionsupporting
confidence: 93%
“…In May 2012, greater 2012 N rates led to more vigorous growth of 'Immortality' TB iris. These results are consistent with those reported for gladiolus (Gladiolus L.) (Khan et al, 2012) and dahlia (Dahlia Cav.) (Younis et al, 2009) of which the height of plants was improved by higher N fertilizer rates.…”
Section: Discussionsupporting
confidence: 93%
“…The results indicated that using autoclaved vermicompost as organic material and autoclaved vermicompost enriched with bacteria formulation increased the yield, quality of corms and flowers of Gladiolus grandiflorus L.. Our results are compatible with the findings of other researchers (Gangaharan and Gopinath, 2000;Atta-Alla et al, 2003;Khan et al, 2012;Singh et al, 2016;Tirkey et al, 2017;Akter et al, 2017). Growth and development of plants is due to the presence of humic acids (Albanell et al, 1988;Joshi et al, 2015) and micro and macronutrients in plantavailable forms (Orozco et al, 1996;Joshi et al 2015) in vermicompost.…”
Section: Discussionsupporting
confidence: 92%
“…Nitrogen, phosphorus, and potassium greatly influence the growth, flower, and tuber production of tuberose (Khan et al, 2012). Nitrogen and phosphorus are required in sufficient quantities to attain better growth and promote flowering (Pandey and Mishra, 2005).…”
Section: Npk On Yield and Yield Attributesmentioning
confidence: 99%
“…Nitrogen and phosphorus are required in sufficient quantities to attain better growth of marigold and promote flowering (Pandey and Mishra, 2005). It was reported that nitrogen, phosphorus, and potassium greatly influence the growth, flower, and tuber production of tuberose (Khan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%